Manajemen Konflik dalam Meningkatkan Kinerja Tim Pendidik - M. Rusni Eka Putra; Wahidin Wahidin; Deni Nofriansyah; Ahmad Gawdy Prananosa; Agus Sutrisno (JOEAI (Journal of Education and Instruction), 2026)
This study aims to examine conflict management as a means to enhance the performance of the educator team in elementary schools in Lubuklinggau City. The study employs a qualitative approach using a phenomenological method. The results indicate that factors such as communication, mediation, negotiation, and deliberation are crucial in managing conflict to improve teacher performance; these elements enable the school principal to identify the information regarding school issues that trigger conflicts while working to resolve them. In conclusion, conflict management—specifically through communication, mediation, negotiation, and deliberation—plays a vital role in enhancing teacher performance.   Keywords: Management, Conflict, Team Performance